(untitled) (Journal of Educational Sciences, 2016)
This article described those prior directions for formation of future specialist’s professional competence and their professional competences which requires to grasp in the learning process. And it gave expression for those contents of training for specialists who have the rich professional knowledge which includes a great sense of responsibility of institutions of higher education, qualified, master of his craft, competitive, have a wide range of vision, fully developed, and have the socio – economic and spiritual development for the growth of the content and the quality of the properties and changes in labor requirements of the competent. It provided the organization for determination of domestic and foreign scientists that named Professional training in higher educational institutions in determining the methodological and theoretical foundations. Modernization of the education system in our country is carried out in three priority areas. In particular, first, shows solicitude for the introduction of modern techniques and technologies into educational organizations ’convenience and learning process. Second, promote the importance of the transforming of teaching and educational process and to improving the quality of educational institutions. And considers it necessary to be work out those special education teacher standards, the need to strengthen teachers’ quality training process in schools and higher education institutions and the functioning of the integrated centers for training and improving teacher’s quality in each region. The third, it described the improving of availability and effectiveness in educational services and establishment of an independent system of professional development.